Generi e modi nella narrativa contemporanea: ipotesi per un “modo ecologico” (Comparatismi, 2025)
Various studies have advanced the need to renew the theoretical vocabulary by replacing the concept of “genre” with that of “mode”, as a more suitable hermeneutic tool for investigating the fluidity and the imaginative and formal contaminations of contemporary fiction. The mode is particularly effective in the case of the environmental theme, whose hybridity makes it difficult to use a blurred category such as that of “ecological genre” or “cli-fi”. This work, after discussing the advantages of using the “mode” instead of the “genre”, aims to reflect on a possible “ecological mode” to integrate with those already proposed by Ceserani (1999) and Bertoni (2018), highlighting above all its typical figural movements. To do this, we will adapt what Frye (1957) wrote regarding narrative weight and the protagonist’s agency as distinctive criteria of modes. In the supposed ecological mode, the human character is situated in a scenario of asymmetric co-agency, within an inventive world characterized by the polarity between infinitely larger forces – such as atmospheric agents – and infinitely smaller forces – such as the vegetal and animal non-human. This hypothesis will be supported by the reading of Barbara Kingsolver’s Flight Behavior (2012), a text that actuates a perspectival expansion aimed at recalibrating the human’s action space within a multiscalar environment.
Keywords: Literary genre; Mode; Cli-fi; Ecocriticism; Flight Behavior